Frequency and visual outcome of Traumatic Cataract - Zaman, Mir; Iqbal, Sofia; Ullah, Sana; Khan, Muhammad Daud (Journal of Postgraduate Medical Institute, 2011)
To assess the frequency causative agents, current treatemtn options, post operative complications and final visual outcome of trauma related cataract. The study was conducted at KIOMS HMC, Peshawar from November 1999 to November 2001. Detailed history with special reference to age, sex mode of injury, causes and circumstances of trauma were recorded. Indications for surgery were traumatic cataract with or without open globe injury. all patients had B scans (ultrasonography) to evaluate the posterior segment. all patients were operated under general anaesthesia. Teh patients were followed up for six months. Traumatic cataract is common cause of visual loss after trauma. Males are affected more than females. nearly half of patients affected are children under the age of 16. Taking necessary precaustions for sports and work can prevent nearly 54% of cataracts. Most common causative agents are stone and wooden sticks.